Survey on replication techniques for distributed system - Ahmad Shukri Mohd Noor; Nur Farhah Mat Zian; Fatin Nurhanani M. Shaiful Bahri (Institute of Advanced Engineering and Science, 2019)
Distributed systems mainly provide access to a large amount of data and computational resources through a wide range of interfaces. Besides its dynamic nature, which means that resources may enter and leave the environment at any time, many distributed systems applications will be running in an environment where faults are more likely to occur due to their ever-increasing scales and the complexity. Due to diverse faults and failures conditions, fault tolerance has become a critical element for distributed computing in order for the system to perform its function correctly even in the present of faults. Replication techniques primarily concentrate on the two fault tolerance manners precisely masking the failures as well as reconfigure the system in response. This paper presents a brief survey on different replication techniques such as Read One Write All (ROWA), Quorum Consensus (QC), Tree Quorum (TQ) Protocol, Grid Configuration (GC) Protocol, Two-Replica Distribution Techniques (TRDT), Neighbour Replica Triangular Grid (NRTG) and Neighbour Replication Distributed Techniques (NRDT). These techniques have its own redeeming features and shortcoming which forms the subject matter of this survey.